Investigation into IGBT transient characteristics and calculation of switching power loss - Hasan, Rifatul; Mustary, Sharmin; Bristy, Nigar Sultana (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.